THE HETERODONT BIVALVE APHRODINA DUTRUGEI (COCQUAND, 1862) FROM THE CENOMANIAN OF JORDAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2005)
The almost equivalved, strongly inequilateral Aphrodina dutrugei (Coquand, 1862) from the Shuayb Formation of the Zarqa area, Jordan, is described. The ammonites collected in the same unit indicate a Late Cenomanian- Early Turonian age. Pdf